The Influence of Special Autonomy Funds and Regional Original Income on Economic Growth in Papua Province (2013–2022) - Jelita Jitmau; Mesak Iek; Pisi Bethania Titalessy; Efannoris Arwimbar (AIBPM Publisher, 2024)
This study examines the impact of Special Autonomy Funds (SAF) and Regional Original Income (PAD) on the economic growth of Papua Province during the 2013–2022 period. Utilizing a quantitative descriptive approach, the research relies on secondary data from the Papua Province Statistics Bureau (BPS) and the Regional Financial Management Agency (BPKAD), focusing on annual financial reports. The data were analyzed using linear regression to measure the relationship between SAF, PAD, and economic growth. The findings reveal that SAF has a positive but statistically insignificant influence on economic growth. This outcome is attributed to suboptimal management and utilization of SAF, which limits its effectiveness in addressing community development needs. Conversely, PAD exhibits a significant positive influence on economic growth, primarily driven by high levels of government expenditure on regional development projects and financing. These results highlight the critical role of efficient resource allocation and fiscal management in promoting sustainable economic progress.